Analisis Dampak Ekonomi Berganda (Multiplier Effect) Pariwisata terhadap Pelaku Usaha dan Pekerja di Pantai Pandawa, Bali - Aditama, Nyoman Mahendra; I Wayan, Mertha (Journal of Tourism and Hospitality Analysis (JoTHA), 2024)
Pandawa Beach is one of the popular tourist attractions in Bali, which is located in South Kuta, Badung. Industrial development carried out by the government as well as the community and also the management of Pandawa Beach, makes Pandawa Beach a tourist attraction that is visited by many tourists every year. The tourism activities that occur on Pandawa Beach can create multiple impacts that can provide economic benefits to the people who participate directly or indirectly in these tourism activities. Therefore, this study aims to determine whether the multiple economic impacts given by the existence of tourism activities are good or vice versa. Respondents in this study were divided into 3: tourists, business owners and workers. The analysis techniques used are descriptive analysis and Keynesian Local Income Multiplier analysis to identify multiple economic impacts on Pandawa Beach. The results show that the multiple economic impact on Pandawa Beach is quite good, with a value of >1, while the direct economic impact value is 1.08, the indirect economic impact is 1.45, and the induction economic impact is 1.58. These results indicate that tourist activities on Pandawa Beach have a very good impact, so they do not harm the community. The suggestions given from the data are addressed to the management, community and government.